(untitled) (Journal of the College of Basic Education, 2022)
Scientific developments and technologies in all fields of life in general and the field of education in particular have led to the emergence of changes in the educational structure and teaching methods based on modern formulas that fit in their entirety and the spirit of the era, and since universities are among the educational institutions that play a major role in the life of society and achieve the desired educational goals, This is because it contributes to addressing the educational problems facing educational institutions, so it develops appropriate solutions for them, and rehabilitates students after their graduation, for example. In addition, the educational design process focuses on the learner, who is the focus of the educational process, and its purpose is to innovate the new and ideal way to train the learner or to achieve the outputs desired and help the learner to learn the easiest results,